The Use of Big Data via 5G to Alleviate Symptoms of Acute Stress Disorder Caused by Quarantine Measures - Hassani, Hossein; Komendantova, Nadejda; Unger, Stephan; Ghodsi, Fatemeh (Frontiers in Psychology, 2022)
This article investigates the role of Big Data in the setup of a psychological stress situation such as the recent pandemic caused by the COVID-19 health crisis. Quarantine measures, which are necessary to mitigate pandemic risk, are causing severe stress symptoms to the human body including mental health. We highlight the most common impacts of uncertainty connected with COVID-19, quarantine measures and the role of Big Data, namely, how Big Data can help alleviating or mitigate these effects by comparing the status quo of current technology capabilities with potential effects of an increase of digitalization on the mental health. We find that, while Big Data helps in the pre-assessment of potentially endangered persons, it also proves to be an efficient tool to alleviate the negative psychological effects of a quarantine. We find evidence in the positive effect of Big Data on the human health condition by assessing the effect of internet usage on mental health in 173 countries. We find positive effects in 110 countries with 90 significant results. However, increased usage of digital media and exclusive exposure to digital connectivity causes negative long-term effects such as a decline in social empathy, which creates an own form of psychological isolation causing again symptoms of acute stress disorder.